On the Formation of Environmental Normative Criteria: Bioethics as a Dead End - Eva Smolková (Studia Ecologiae et Bioethicae)
The need to reflect upon the environment and the creation of a concept of environmental philosophy resonated in the philosophical thinking of the 1980s and 1990s. It seems that the advent of national and international institutions, which were “given” the responsibility for environmental issues, the importance of creating environmental principles, and pursuing environmental goals, has seemingly dwindled. The relationship with the environment has turned into the relationship of a citizen to his or her country, and with the principles and standards taking the form of legal regulations, the issue quickly became a matter of abiding by the law. Whilst discussion on how the normative criteria are set continued, its focus shifted to the questions of how and why they should be gradually made stricter, factoring in the economic interests of enterprises, and the time needed for setting up the processes, and developing new technologies. Environmental philosophy gradually integrated into bioethics in a broader context. This paper discusses the question of whether the integration of the environmental philosophy of bioethics helped to better promote the idea of environmental responsibility and environmental ethics, or otherwise. The study aims to initiate a discussion on whether this was a step in the right direction, and to assess how effective it was in relation to the pursuit and formation of environmental criteria.